To Live for a Future: A Reply to My Critics - Craig, Anita P (PINS-Psychology in Society, 2026)
It is disappointing that neither reply deals with the difficult issue of how to examine and articulate the way we live now, especially those ways that are only recognisable in dim outline, as it were. Name-calling is hardly a fruitful direction to pursue. Scattered about the replies are terms such as prophet, prophet-politician, suspect racist, a whiny, worried, gutsy, fearful white person with obsessive tendencies, a modernist (some kind of insult!) and common citizen. All that this does is to suggest that we should add "name-calling" to the list of sloppy thought habits. From Tony Leon and dissociated conspiracy theory to army provisions - military equipment, the intentions/problems assumed to underlie the text are now there for all to see, but whether these are indeed motivating an examination such as I attempt, is an issue that falls by the way side.